Paving the Way for Sustainability: Can Green Infrastructure Drive Energy Efficiency in South Africa? - Ogunsola, Akindele John; Zwane, Talent Thebe (Journal of Ecohumanism, 2025)
The persistent energy inefficiency in South Africa, driven by inconsistent renewable energy policies, weak institutional frameworks, and environmental degradation, thus underscores the dire need for an exhaustive evaluation of green infrastructure development. This paper explores the relationship between green infrastructure and energy efficiency between 2000 and 2023, using the energy ladder theory to analyze how the quality of institutions moderates such a relationship, which was analyzed by the Prais-Winsten estimation method. Major findings reveal that renewable energy generation and hydropower contribute to a significant reduction in carbon emission intensity and primary energy consumption, while forest cover and waste management contribute to improved energy efficiency. In fact, the institutional quality turns out to be a crucial moderator, reinforcing the positive impacts of green infrastructure, mainly renewable energy investment and hydropower development. The Granger causality test also presents a two-way complicated relationship between energy intensity and green energy investments, suggesting the interaction of energy efficiency policy. The study ends with the suggestion that reforms in institutional setup are a must to capture the environmental and economic potential of green infrastructure. Embedding policies of renewable energy expansion within a package of governance reforms is key to driving sustainable energy development in South Africa.